2013
DOI: 10.7813/2075-4124.2013/5-4/b.68
|View full text |Cite
|
Sign up to set email alerts
|

The viewpoints of physics teacher candidates towards the concepts in special theory of relativity and their evaluation designs

Abstract: In this study, the viewpoints of physics teacher candidates at undergraduate level towards the concepts in special theory of relativity and the interpretations they made about these concepts were investigated. The viewpoints of the teacher candidates towards the concepts in the subject of special theory of relativity were revealed with six open ended questions prepared by the writers who are physics teachers as well. The research is a qualitative study and the study was conducted with eighteen teacher candidat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 4 publications
0
5
0
Order By: Relevance
“…It attracts attention that especially female students have more difficulties than male students in this topic. According to the body of literature, the students are inclined to use classical physics while answering the questions about relativity (Turgut et al, 2013;Pietrocola and Zylberztajn, 1999). Even if the students solve the problems about special relativity, they have difficulties in changing the classical ways of thinking in the process of comprehending the main concepts of relativity (Arriassecq and Greca, 2012).…”
Section: Conclusion and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It attracts attention that especially female students have more difficulties than male students in this topic. According to the body of literature, the students are inclined to use classical physics while answering the questions about relativity (Turgut et al, 2013;Pietrocola and Zylberztajn, 1999). Even if the students solve the problems about special relativity, they have difficulties in changing the classical ways of thinking in the process of comprehending the main concepts of relativity (Arriassecq and Greca, 2012).…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…Studies should be made to research the reasons of it. In the body of literature, attention is drawn to the difficulties of the students about the theory of relativity (DidişKörhasan and Özcan, 2015;Turgut et al, 2013;Ogborn, 2005). Angell et al (2004) remark that the students did not regard mathematics as a problem but the teachers complained about the deficiencies in the mathematical skills of the students, in the results of their study in which they searched the students' and tearchers' opinions about physics lessons.…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…This result means that the students had an increased number of misconceptions about mass at the end of the course. Turgut et al (2013) have also reported that there is an increase after teaching in the number of students who think that mass increases at speeds close to the speed of light. Selçuk (2011) has stated that this misconception increases due to students' inaccurate generalizations and intuitive ideas.…”
Section: Necatibey Eğitim Fakültesi Elektronik Fen Ve Matematik Eğitimi Dergisi Necatibey Faculty Of Education Electronic Journal Of Sciementioning
confidence: 91%
“…Moreover, it was highlighted that the students had difficulty understanding the concept of reference system. In their study on 30 physics education students, Turgut, Gurbuz, Salar & Toman (2013) lessons given during the study contributed to the understanding of the concept of relative time.…”
Section: Related Research About Special Relativitymentioning
confidence: 99%
“…As a result of the literature review, a limited number of studies examining the concepts of students regarding special relativity and relationships between the concepts could be attained in the national literature (Özcan and Abak, 2007;Özcan, 2009;Sezgin Selçuk, 2011;Turgut, Gürbüz, Salar and Toman, 2013;İngec, Taşkın and Gürsoy, 2016;İngec and Tinni, 2016;Önsal and Güneş,2016). It is obvious that there is a need for studies examining the knowledge levels of students regarding special relativity, determining present conceptual mistakes and aiming to develop conceptual tests intended for measuring the conceptual knowledge.…”
Section: Extended Abstractmentioning
confidence: 99%